2005
DOI: 10.1590/s0001-37652005000400009
|View full text |Cite
|
Sign up to set email alerts
|

An overview of chagasic cardiomyopathy: pathogenic importance of oxidative stress

Abstract: There is growing evidence to suggest that chagasic myocardia are exposed to sustained oxidative stressinduced injuries that may contribute to disease progression. Pathogen invasion-and replication-mediated cellular injuries and immune-mediated cytotoxic reactions are the common source of reactive oxygen species (ROS) in infectious etiologies. However, our understanding of the source and role of oxidative stress in chagasic cardiomyopathy (CCM) remains incomplete. In this review, we discuss the evidence for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 141 publications
1
32
0
3
Order By: Relevance
“…Recent studies have shown that T. cruzi lacking TcAPx is still capable of infecting cultured mammalian cells, albeit at a reduced level, and can still establish an infection in the mouse model of CD (20). Although the enzyme does not seem to be essential for parasite infectivity, its enhanced expression may represent an additional skill for the parasite to deal with host-derived oxidant toxicity both in the acute and chronic stages of the disease (6,21).…”
Section: Significancementioning
confidence: 99%
“…Recent studies have shown that T. cruzi lacking TcAPx is still capable of infecting cultured mammalian cells, albeit at a reduced level, and can still establish an infection in the mouse model of CD (20). Although the enzyme does not seem to be essential for parasite infectivity, its enhanced expression may represent an additional skill for the parasite to deal with host-derived oxidant toxicity both in the acute and chronic stages of the disease (6,21).…”
Section: Significancementioning
confidence: 99%
“…Besides ROS, reactive nitrogen species (RNS), which are formed from the reaction of nitric oxide (NO) with superoxide radical 6,7 , may also lead to oxidative stress, responsible for many pathological conditions such as chagasic cardiomyopathy 8 .…”
Section: Article/artigomentioning
confidence: 99%
“…During the chronic phase, diffused inflammatory infiltrate persists in the myocardium (reviewed in Refs. 5,6). Besides infiltration of inflammatory infiltrate, cardiomyocytes are also reported to produce cytokines in response to T. cruzi infection (7), although the signaling events are not known.…”
mentioning
confidence: 99%